Patterns of Somatic Diagnoses in Older People with Intellectual Disability: A Swedish Eleven Year Case–Control Study of Inpatient Data. Issue 1 (6th November 2015) - Sandberg, Magnus; Ahlström, Gerd; Kristensson, Jimmie
Abstract : Background: Knowledge about diagnoses patterns in older people with intellectual disabilities is limited. Methods: The case group ( n = 7936) comprised people with intellectual disabilities aged 55 years and older. The control group ( n = 7936) was age matched and sex matched. Somatic inpatient diagnoses (2002–2012) were collected retrospectively. Results: Several diagnoses were in several years significantly more common in the case group, particularly infections [odds ratio (OR) 1.78–4.08]; nervous system (OR 2.06–31.75); respiratory (OR 1.78–4.08) and genitourinary diseases (1.59–11.50); injuries, unspecified symptoms (OR 1.56–4.27); and external causes of morbidity (OR 1.53–4.08). The oldest in the case group had significantly less occurrence of tumours (OR 0.26–0.51), cardiovascular (OR 0.42–0.72), and musculoskeletal diseases (OR 0.32–0.53) than controls. Conclusions: Older people with intellectual disabilities have higher numbers of some diagnoses, but lower numbers of others. Further research on the reasons for the unique pattern of diagnoses in this group is required.